Spectral analysis of spin noise in an optically spin-polarized stochastic Bloch equation driven by noisy magnetic fields - Minwoo M. Kim; Sangkyung Lee (AIP Advances, 2024)
We theoretically analyze an optically spin-polarized collection of atoms, which serves as a basis for atomic sensors. Assuming that the intrinsic atomic spin projection noise is negligible, we provide the closed-form autocorrelation function and the power spectral density (PSD) of the solution to a noisy version of an optically pumped Bloch equation, wherein each component of the external magnetic field is subjected to white noise. We conclude that noise in the bias B-field direction does not affect the autocorrelation function, up to first order in white noise covariance amplitudes. Moreover, the noise terms for the remaining two axes make different contributions to the magnetic noise-driven spin PSD; in particular, the contribution corresponding to noises perpendicular to the probing direction dominates at high frequencies. Some results concerning the second (and higher)-order terms are given. In particular, we anticipate a decrease in the effective Larmor frequency despite an increase in the magnetic field magnitude in the case of anisotropic transversal B-field noises. The analytic results are supported by Monte Carlo simulations employing the Euler–Maruyama method. The analytic methodology is applied to the case of a Bell–Bloom magnetometer, which reveals a non-linearity in the PSD of the magnetometer output and also a broadening effect due to magnetic field noise.